Understanding Kubrick's '2001: A Space Odyssey'. Representation and interpretation - Fenwick, James (Intellect Ltd, 2018)
Scholars have been studying the films of Stanley Kubrick for decades. This book, however, breaks new ground by bringing together recent empirical approaches to Kubrick with earlier, formalist approaches to arrive at a broader understanding of the ways in which Kubrick?s methods were developed to create the unique aesthetic creation that is '2001: A Space Odyssey'. As the fiftieth anniversary of the film nears, the contributors explore its still striking design, vision, and philosophical structure, offering new insights and analyses that will give even dedicated Kubrick fans new ways of thinking about the director and his masterpiece.